2018
DOI: 10.1002/ecy.2191
|View full text |Cite
|
Sign up to set email alerts
|

The response of big sagebrush (Artemisia tridentata) to interannual climate variation changes across its range

Abstract: Understanding how annual climate variation affects population growth rates across a species' range may help us anticipate the effects of climate change on species distribution and abundance. We predict that populations in warmer or wetter parts of a species' range should respond negatively to periods of above average temperature or precipitation, respectively, whereas populations in colder or drier areas should respond positively to periods of above average temperature or precipitation. To test this, we estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 53 publications
(126 reference statements)
9
56
0
Order By: Relevance
“…Fig. Secondly, it demonstrates that warming in cool sites creates a positive cover response, and vice versa in warm sites, similar to Kleinhesselink and Adler (2018) who reported that colder portions of the sagebrush range have a positive response in cover in warmer years, while warmer areas have a negative response. Cool WYTMIN sites have the greatest increase in WYTMIN, smallest increase in WYTMAX, and greatest decrease in WYPRCP (Fig.…”
Section: Fractional Component Slopes By Climatesupporting
confidence: 85%
See 1 more Smart Citation
“…Fig. Secondly, it demonstrates that warming in cool sites creates a positive cover response, and vice versa in warm sites, similar to Kleinhesselink and Adler (2018) who reported that colder portions of the sagebrush range have a positive response in cover in warmer years, while warmer areas have a negative response. Cool WYTMIN sites have the greatest increase in WYTMIN, smallest increase in WYTMAX, and greatest decrease in WYPRCP (Fig.…”
Section: Fractional Component Slopes By Climatesupporting
confidence: 85%
“…5C shows that shrub and sagebrush cover increase in sites with the cooler average WYMIN below~17°C and decrease in warmer sites. 5C), again concurring with Kleinhesselink and Adler (2018). 5D).…”
Section: Fractional Component Slopes By Climatesupporting
confidence: 75%
“…Demographic parameters are key among these because they provide a mechanistic link between population processes, climate covariates, and population dynamics (Grosbois et al, ). Studies that link demographic rates to climate are still relatively rare (Amburgey et al, ; Kleinhesselink & Adler, ; Scridel et al, ). We suggest that multi‐species demographic monitoring combined with directed research relating climate to demographic parameters can provide an important tool for guiding conservation of species assemblages in the face of climate change (Saracco, Fettig, San Miguel, Mehlman, & Albert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study species, big sagebrush, is a keystone species in the imperiled sagebrush steppe ecosystem (Miller et al, ). Prior studies have emphasized the role of climate and topography in determining sagebrush species distributions (Kleinhesselink & Adler, ; Schlaepfer, Lauenroth, & Bradford, ; Still & Richardson, ; Tredennick et al, ). However, sagebrush populations, especially in the Great Basin, are declining due to increases in fire frequency and are often additionally altered by intensive restoration efforts.…”
Section: Discussionmentioning
confidence: 99%